2018
DOI: 10.1002/jsfa.9098
|View full text |Cite
|
Sign up to set email alerts
|

Carbon footprint of organic beef meat from farm to fork: a case study of short supply chain

Abstract: The identification of the major sources of GHG emissions associated with organic beef produced and consumed in a local food network may stimulate debate on environmental issues among those in the network and direct them toward processes, choices and habits that reduce carbon pollution. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 15 publications
0
26
1
Order By: Relevance
“…Local food systems using organic methods increase worldwide, but little is known about their carbon footprint. Vitali et al (2018) [100] examined the production of greenhouse gases in short supply chains related to the marketing and sale of organic beef. They found that farm activities and home consumption had the greatest global warming potential in the product path.…”
Section: Environmental Aspects Of Short Supply Chainsmentioning
confidence: 99%
“…Local food systems using organic methods increase worldwide, but little is known about their carbon footprint. Vitali et al (2018) [100] examined the production of greenhouse gases in short supply chains related to the marketing and sale of organic beef. They found that farm activities and home consumption had the greatest global warming potential in the product path.…”
Section: Environmental Aspects Of Short Supply Chainsmentioning
confidence: 99%
“…Food supply chains produce Greenhouse gases (GHGs), mainly CO 2 e, throughout all the stages of the life cycle from farming processes through to warehousing, production, storage, distribution, retailing, consumption and disposal of waste (Garnett, 2006). Many studies have examined the CO 2 e generated throughout a FSC; e.g., Garnett (2006) Garnett (2011), López et al (2015), Porter et al (2018) and Vitali et al (2018). There is significant evidence in the literature on attempts made in reducing the CO 2 e associated with FSC (Gadema and Oglethorpe, 2011;Oglethorpe and Heron, 2013;Ramanathan et al, 2014).…”
Section: Fsc (Fsc): Uk Fruits and Vegetablesmentioning
confidence: 99%
“…Scientific evidence suggests that global climate change poses a great risk to human society, and Earth's climate has recently changed rapidly, largely due to the rapid increase in anthropogenic greenhouse gas (GHG) emissions in recent decades . Therefore, an increasing number of people are urging for the development and adoption of effective measures to reduce global GHG emissions . In response to the international demand for a drastic reduction in GHG emissions, China has promised that carbon emissions will peak by approximately 2030.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Therefore, an increasing number of people are urging for the development and adoption of effective measures to reduce global GHG emissions. 4,5 In response to the international demand for a drastic reduction in GHG emissions, China has promised that carbon emissions will peak by approximately 2030. Moreover, China has promised to strive for a peak as soon as possible, with the goal of carbon dioxide emissions per unit of gross domestic product falling 60-65% from the levels in 2005.…”
Section: Introductionmentioning
confidence: 99%